Perubahan Pola Hidup Anak Sebelum dan Selama Pandemi Covid-19 - Sri Widayati; Irma Novita (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2020)
The world is so preoccupied by pandemic covid 19 that it has an impact on aspects of life, especially on children's life patterns. This study aims to determine differences in life patterns of early childhood related before and during the co-19 pandemic. A total of 381 early childhoods were targeted in this study. The approach used in research is a quantitative approach to the type of survey analysis. Collecting data in this study with online questionnaire techniques with a Likert scale. The analysis technique in this study used paired sample t test. The results showed a transition related to changes in lifestyle of early childhood before and during the co-19 pandemic. This study provides the impression that parents are more involved in adjusting children's lifestyles during the co-19 pandemic.